2021
DOI: 10.3390/cells10030594
|View full text |Cite
|
Sign up to set email alerts
|

Facial Rejuvenation with Concentrated Lipograft—A 12 Month Follow-Up Study

Abstract: Lipofilling is a popular technique to treat volume loss in aging patients. The isolated adipose tissue is composed of adipocytes and stromal vascular fraction cells, which include adipose-derived stem cells (ASC). We hypothesize that the patient’s wrinkle severity scale (WSS) and patient’s satisfaction on the global aesthetic improvement scale (GAIS) can be improved after using concentrated lipoaspirate. Fourteen patients (54 years ± 11.09 years) with volume loss in the midface area underwent waterjet-assisted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In 17% of patients, fat tissue necrosis or oil cysts were detected post-operatively without the need for biopsies or revision surgery. The progressive improvement and optimization, among others of the preparation technique by the Cell Enriched Lipotransfer (CELT) method, will further improve the complication and healing rates with a higher engraftment (over 90%) of the lipoaspirate in the future [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 17% of patients, fat tissue necrosis or oil cysts were detected post-operatively without the need for biopsies or revision surgery. The progressive improvement and optimization, among others of the preparation technique by the Cell Enriched Lipotransfer (CELT) method, will further improve the complication and healing rates with a higher engraftment (over 90%) of the lipoaspirate in the future [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we can transplant the mechanically stable fat (after the second centrifugation) with properties comparable to those of the target tissue, thereby leading to satisfying long-term results. This has already been demonstrated in one of our clinical studies on facial lipofilling, offering good long-term results over one year, even in areas of mechanical stress such as the nasolabial fold or periorbital area [ 26 ].…”
Section: Discussionmentioning
confidence: 82%
“…In previous work, we demonstrated that enriched autologous fat grafting offers good long-term results in patients presenting midface deficiency, with the procedure clearly improving facial volume loss and skin quality. [3] In this study, we examine the long-term outcomes for patients with congenital breast asymmetry who underwent either lipograft or silicone implant augmentation. Since both surgical methods are described differently in the literature, we present the protocols we implemented below.…”
Section: Introductionmentioning
confidence: 99%